2021
DOI: 10.3389/fpsyt.2021.577103
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Psychological Disorders and Alternative Medicine in Saudi Participants

Abstract: Background: This study was designed to investigate Saudis' attitudes toward mental distress and psychotropic medication, attribution of causes, expected side effects, and to analyze participants' expectations toward alternative or complementary medicine using aromatic and medicinal plants, through a survey.Method: The study included 674 participants (citizens and residents in Saudi Arabia) who were randomly contacted via email and social media and gave their consent to complete a questionnaire dealing with 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…This might be due to the presence of apiol in the P. anisum active fraction. It has been reported in previous studies that apiol is a very potent appetite stimulant and also promotes the enzymatic secretions of the digestive tract [30]. From all the above discussions, it is quite clear that the GC-MS analysis reported the presence of oxadiazole compounds in the P. anisum active fraction (P.aAF).…”
Section: Discussionmentioning
confidence: 71%
“…This might be due to the presence of apiol in the P. anisum active fraction. It has been reported in previous studies that apiol is a very potent appetite stimulant and also promotes the enzymatic secretions of the digestive tract [30]. From all the above discussions, it is quite clear that the GC-MS analysis reported the presence of oxadiazole compounds in the P. anisum active fraction (P.aAF).…”
Section: Discussionmentioning
confidence: 71%
“…and safflower ( Carthamus tinctorius ), suggested 11 times each. Most of the reported plants and herbs have been documented for their psychological properties such as neuroprotective, anxiolytic, antidepressant, and anti-stress features via the inherent phytochemicals and secondary metabolites [ 23 ]. Surprisingly, only 18.8% of the participants agreed that medicinal and aromatic plants could treat psychological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, only 18.8% of the participants agreed that medicinal and aromatic plants could treat psychological disorders. Participants (82%) reported that physicians are the most trustful and preferred source of information about alternative and complementary medicine [ 23 ].…”
Section: Discussionmentioning
confidence: 99%